The Influence of Parenting on Juvenile Delinquency - Siti Aisah (Journal of Religion and Social Community | E-ISSN : 3064-0326, 2024)
Juvenile delinquency has now occurred in almost all corners of the country, especially in children who are still in school, as happened at SMA Negeri Plus Sukowono, juvenile delinquency that occurs is smoking and skipping classes in class. The factors that cause the emergence of juvenile delinquency are one of them rather than parental parenting. Parenting styles that cannot adjust to the needs of children then affect the development of socialization in their environment. Parenting consists of authoritarian parenting, democratic parenting, and permissive parenting. The parenting style that causes the delinquency at SMA Negeri Plus Sukowono is a permissive and authoritarian parenting style. The purpose of this study is to find out how the parenting style of adolescent delinquency at SMA Negeri Plus Sukowono is. The research method carried out in this study is to use a quantitative descriptive approach of respondents consisting of 34 adolescents in class X with sampling techniques by means of simple random sampling, and collection using questionnaires. The formulation of the problem that will be taken in this study is the influence of parental parenting on juvenile delinquency?, how does parental parenting affect juvenile delinquency?, and what are the factors that affect adolescent delinquency?.